COMBINING ABILITY ANALYSIS IN DIALLEL CROSSES OF WHEAT (TRITICUM AESTIVUM L.) - JAISWAL, KUNDAN KUMAR; S. MARKER; BINOD KUMAR (The Bioscan, 2013)
In order to realize the combining ability of wheat, 15 hybrids were synthesised in a 6 x 6 diallel fashion excluding reciprocals and to isolate the good combiner for various yield component traits. Results on gene action and combining ability indicated that both additive and non-additive gene effects are importance in governing the expression of these yield component traits. Single seed descent method can be applied to exploit additive gene effects whereas non-additive gene effects could be valuable in hybrid wheat breeding programs. Three parents viz.; K-8962, Kalyansona and Sonalika were identified as most promising parents due to having good general combining ability for grain yield and some of the other important traits. Among the crosses significant and desirable sca effects in order of merit for yield and yield contributing traits were exhibited by HUW 510 x PBW 373, HUW 510 x HUW 234, Sonalika x K-8962,Sonalika x HUW 234 and Kalyansona x K-8962. Therefore, these crosses could be utilized for further selection of high yielding progenies to achieve a quantum jump in improvement of wheat crop.